2015
DOI: 10.4274/tjo.43815
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and the Eye

Abstract: Pregnancy causes significant changes in all systems of the body. Although most of them are physiological, they may also lead to pathological consequences. The resulting pathological changes may occur for the first time or existing diseases affected by pregnancy can become more serious or change course. Diseases specific only to pregnancy may arise. Like all systems of the body, the visual system is also affected by pregnancy, developing a wide range of physiological and pathological changes. Knowing the ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 52 publications
1
33
0
4
Order By: Relevance
“…The change in the eyes refractive index during pregnancy could be due to hormonal changes which cause fluid retention in the cornea. [ 14 15 18 ] A previous study[ 19 ] has also related this discovery to increase in the lens curvature which invariably lead to a myopic shift. Previous studies[ 11 15 ] have suggested that the presence of comorbidities such as diabetes mellitus and hypertension to be responsible for the reduced VA and refractive changes observed during pregnancy;[ 20 ] however, this is not true of the present study because participants with associated co-morbidities were excluded.…”
Section: Discussionmentioning
confidence: 92%
“…The change in the eyes refractive index during pregnancy could be due to hormonal changes which cause fluid retention in the cornea. [ 14 15 18 ] A previous study[ 19 ] has also related this discovery to increase in the lens curvature which invariably lead to a myopic shift. Previous studies[ 11 15 ] have suggested that the presence of comorbidities such as diabetes mellitus and hypertension to be responsible for the reduced VA and refractive changes observed during pregnancy;[ 20 ] however, this is not true of the present study because participants with associated co-morbidities were excluded.…”
Section: Discussionmentioning
confidence: 92%
“… 2 , 76 On the other hand, many ocular symptoms are manifestations of an underlying systemic disease which develops or exaggerates with hormonal surges in pregnancy. 77 Overall, these pathologies can be divided into existing and preexisting ocular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“… 10 On the other hand, estrogen surge has a documented effect on immunological status by which it can influence preexisting autoimmune diseases such as Graves' ophthalmopathy, multiple sclerosis and posterior scleritis, and uveitis. 32 , 74 , 77 However, alteration of previously established ocular disease might differ substantially over pregnancy trimesters, probably due to the variation in serum levels of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a known risk factor for CSCR. 15 It occurs in 1% patients with severe pre eclampsia and 10% of patients with eclampsia. 16,17 Raised blood pressure in pre eclampsia causes ischaemia of choroid which then causes CSCR.…”
Section: Discussionmentioning
confidence: 99%